CEOs Accounting Background and ESG Disclosure: Empirical Evidence of Indonesian Listed Companies - Muhammad Sabrian Oehoedoe; Adib Minanurohman; Nurul Fitriani (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
The main objective of this study is to provide empirical evidence that educational background and accounting experience of CEOs have a relationship with environmental, social, and governance (ESG) disclosure. Data was gathered from all listed companies on the Indonesia Stock Exchange from 2010 to 2020. 533 firms that published sustainability reports were selected as the sample for the research. The results indicate that CEOs with an educational background in accounting and work experience in accounting field, especially those who have worked at BIG4 accounting firms, have a significantly positive relationship with ESG disclosure. This means that CEOs who are well-versed in accounting are more sensitive to environmental issues and therefore, more likely to disclose more information about ESG. The findings suggest that CEOs with an accounting background are more environmentally conscious and can play a crucial role in expanding ESG disclosure.